Philosophy of Religion After »Religion« - Rodgers, Michael Ch. (Religion in Philosophy and Theology, 2021)
Neuere historische Studien zeigen, dass wir uns Religion nicht immer so vorgestellt haben, wie wir es heute oft tun – als einen besonderen Bereich des Lebens oder der Gesellschaft. Der vorliegende Band versucht, das philosophische Studium der Religion über die Grenzen unseres modernen, begrenzten Verständnisses von dem, was als »Religion« zählt, hinaus zu bewegen.InhaltsübersichtRichard Amesbury: Introduction: Making the Reflexive Turn in Philosophy of Religion – Sonia Sikka: »Religion« under Erasure: Why the Concept is Problematic and Why We Still Need It – Timothy D. Knepper: Why Philosophers of Religion Don't Need »Religion« – at least not for now – Dwayne Tunstall: An Essentialist in Critical Religion Land, Or, How Fitzgerald's Deconstructive Genealogy of Religion Is Compatible with an Essentialist Concept of Religion – J. Aaron Simmons: Vagueness and Its Virtues: A Proposal for Renewing Philosophy of Religion – Vincent Lloyd: Race and the Philosophy of Religion – Jin Y. Park: Nothingness and Self Transformation: Kim Iryŏp, Tanabe Hajime, and Jacques Derrida on Religious Practice – Robert Cummings Neville: Whether Religion Is a Proper Subject of Study